Integrative and inclusive genomics to promote the use of underutilised crops - Shorinola, Oluwaseyi; Marks, Rose; Emmrich, Peter; Jones, Christopher S.; Odeny, Damaris Achieng; Chapman, Mark A. (Nature Publishing Group, 2023)
Underutilised crops are important for diversifying food systems. The genomics of these crops should not be done in isolation but should align with their breeding and capacity building strategies while leveraging advances made in major crops. Underutilised crops or orphan crops are important for diversifying our food systems towards food and nutrition security. Here, the authors discuss how the development of underutilised crop genomic resource should align with their breeding and capacity building strategies, and leverage advances made in major crops.